The Impact of Depression on Undergraduate Students’ Educational Performance: A Case of Nawalparasi and Chitwan Districts (OCEM Journal of Management, Technology & Social Sciences, 2024)
Depression is a growing concern among college students, including Nepalese students. Identifying its origin holds the potential to enhance mental health assistance and strategies, fostering a more supportive academic atmosphere. This research investigated the impact of depression on the academic performance of undergraduates. Employing a quantitative research approach, the survey questionnaire was used as the primary tool for data collection, and descriptive statistics were used for data analysis. The sample consisted of two hundred and one (N = 201) undergraduates selected from Oxford College of Engineering and Management, selected through random sampling to ensure representativeness. The results of this study show a positive association between academic stress and the impact of depression on undergraduate students’ educational performance. Further the results show a negative association between financial pressure and family relationship problems and the impact of depression on undergraduate students’ educational performance. However the result shows no association between the social isolation and the impact of depression on educational performance. This study’s implications would offer benefits to policymakers, teachers, parents, colleges, and universities alike in understanding the current issue of depression in undergraduate students’ performance. This study is limited to specific area, so we can’t strongly suggest to generalize the current results in other similar cases.